Uzlah Perspektif Ibn 'Athaillah al-Sakandari - Khoiri, Imam (Jurnal Penelitian Ilmu Ushuluddin, 2021)
The sparkling "progress" of modernism looks very majestic and luminous. Modernization is the process of changing traditional society into a modern society, marked by changes in economic, social, and political systems. The changes that brought progress were reversed with the condition of modern human spirituality which experienced drought and decline. Therefore, a Sufism approach is needed that cultivates the heart, taste, and soul and balances the rational and experimental approaches that develop in modern society. The purpose of this study is to describe Ibn 'Athaillah al-Sakandari's views on uzlah and to analyze the suitability of uzlah in today's times. This is a qualitative research that uses a literature study approach. The analytical method used is the content analysis technique. The results of this study indicate that the uz that was written by Ibn Athaillah was not a form of activity that was carried out throughout life, but was limited to taking time to isolate oneself from the crowd. Because that way you can use meditation to the fullest. Uzlah is also an effort for modern humans to reflect and think about problems and find solutions in life so that they can get closer to Allah. Because the result of uzlah is not leaving the affairs of the world, but being able to live it with responsibility, discipline and upholding God's commands. The results of this research are expected to be practical in order to maintain the freshness of spirituality and reason.